The Relationship Between Family Support and Anxiety in Primigravida Pregnant Women in the Third Trimester - Asmima Yanti; Ita Susanti; Nurromsyah Nasution (Lembaga Pengembangan Kinerja Dosen, 2022)
Family support is assistance that can be given to other families in the form of goods, services, information, and advice which makes the recipient of support feel loved and appreciated. In this case, family support will bring a sense of joy, security, satisfaction, and comfort that makes pregnant women feel emotionally supported which will affect their mental well-being. Objective: This study aims to determine the relationship between family support and anxiety in Primigravida pregnant women in the third trimester in the work area of the Simeulue Tengah Health Center UPTD, Simeulue Regency. Method: This research method is an analytical survey with a cross-sectional approach with a sample size of 36 respondents using the total sampling technique. The study began on December 16-20, 2022. Results: Family support is in the sufficient category with 16 respondents (44.4%) and the level of anxiety in Primigravida pregnant women in the third trimester is in the moderate and severe categories, each with 12 respondents (33.3%). Conclusion: Based on the results of the study, it was found that there was a relationship between family support and anxiety levels in Primigravida pregnant women in the third trimester at the UPTD Simeulue Tengah Health Center, Simeulue Regency with a p-value = 0.043. Suggestion: It is hoped that medical personnel at the Health Center can provide counseling to families who have pregnant women.